Las habilidades gerenciales de los emprendedores del sector turístico de la Parroquia de Malacatos, Cantón Loja, Provincia Loja - Hidalgo Monteros, Maria Karolina (2023)
The present research work called "MANAGEMENT SKILLS OF THE ENTREPRENEURS OF THE TOURISM SECTOR IN THE PARISH OF MALACATOS, CANTON LOJA, PROVINCE OF LOJA" has as general objective, to determine the level of managerial skills of entrepreneurs in the tourism sector of the Parish Malacatos, for this it was essential to raise specific objectives that helped in the development of this research and delimit the problem, without leaving aside the investigation of a theoretical framework of the topic in question and the collection of data that facilitated an analysis of the theoretical aspects, which allowed to contribute with alternatives for the improvement of the managerial skills of the entrepreneurs of the tourism sector. In the search for results, 35 managers of tourism companies were consulted, where a transversal type of research was developed, in which through surveys it was found that the levels of managerial skills in general are at a medium level; this referring to the fact that in some items of the different skills, it is necessary to implement alternatives that allow to effectively improve the administration of enterprises, in order to generate a business progress suitable to compete. It is important to emphasize that through this research it is concluded that the main causes of the low performance of the enterprises are in the lack of training, innovation, inadequate personnel selection process, lack of innovation in the work for workers, feedback to workers by the managers of the companies. In view of the above, it became evident the importance of seeking solutions that contribute to the improvement of the quality of services, knowledge and training in management skills, in order to improve the enterprises in the tourism sector of the Malacatos Parish, in such a way that alternatives for improvement were proposed, which consists in the training of management skills to managers, employees and workers.